2022-RA-579-ESGO A phase II study assessing safety and efficacy of cabozantinib for advanced or metastatic cervical carcinoma after platinum treatment failure (CABOCOL study). (20th October 2022) - Coquan, Elodie; Lequesne, Justine; Colomba, Emeline; Frenel, Jean-Sébastien; Abdeddaim, Cyril; D'Hondt, Véronique; Castera, Marie; Abadie-Lacourtoisie, Sophie; Dubot, Coraline; Brachet, Pierre-Emmanuel; Leconte, Alexandra; Clarisse, Bénédicte; et al.
Abstract : Introduction/Background: The addition of bevacizumab and pembrolizumab to platinum-based chemotherapy improves survival in advanced/metastatic cervical cancer (a/m CC). However, few therapeutic options are available after progression, associated with a poor prognosis. Cabozantinib, an oral small molecule tyrosine kinase inhibitor targeting several receptor tyrosine kinases known to influence tumor growth, metastasis, and angiogenesis, represents a potential active treatment in CC. CABOCOL study concomitantly assessed the efficacy and safety of cabozantinib monotherapy in a/m CC after failure to platinum-chemotherapy (NCT04205799 ) Methodology: CABOCOL was a single-arm two-stage multicenter phase II trial. Using a Bryant-and-Day design, the primary endpoint was based on both clinical efficacy and safety: the 3-month disease control rate (DCR) and the proportion of patients experiencing gastro-intestinal (GI) or genito-urinary (GU) perforation/fistula grade ≥2 within 1 month after the end of treatment. Considering πEfficacy0 =30%/πEfficacy1 =50% the unacceptable/acceptable 3-month DCR, and πToxicity0 =25%/πToxicity1 =10% the unacceptable/acceptable perforation/fistula rate, and a 10% drop-out rate, 57 patients were needed (51 assessable): p_Efficacy ≥21/51 and p_Toxicity ≤9/51 will allow considering the study as positive. Cabozantinib was administered at the daily oral dose of 60 mg in a 4-week cycle, up to disease progression or unacceptable toxicity. Results: From January 2020 to December 2021, 57 patients were enrolled (54 assessable): median age 56 years, 28 (52%) pre-treated by bevacizumab, median follow-up 7.4 months. For primary endpoint, 25/54 (46.3%) patients had disease control at 3 months and 6/54 (11.1%) patients presented a Grade ≥2 GU/GI fistula/perforation (5 fistula/1 perforation). Overall response rate was 9.3% (5/54), with no complete response. Median progression-free and overall survivals were 2.8 [95%CI: 2.5–4.6] and 8.9 [6.7–14] months, respectively. Toxicity-related dose reduction was observed for 26 patients. Grade ≥3 treatment-related adverse events were GI toxicities (13% G3, 2% G5), hypertension (7.5% G3), asthenia (14.8% G3). Conclusion: Cabozantinib monotherapy showed promising efficacy with manageable toxicity in a/m CC.